24/7 news network: A paradigm shift in the media industry - Nuzuli, Ahmad Khairul (Universitas Negeri Yogyakarta, 2024)
This research aims to investigate the role of 24/7 news networks in transforming how the media industry presents, consumes, and interacts with news. To achieve this goal, the study conducts a literature review on the development and evolution of 24/7 news networks and their impact on society. The analysis results show that 24/7 news networks have significantly changed the media landscape. Firstly, their ability to deliver news instantly and in real-time has shifted traditional news reporting models that relied on print editions or scheduled broadcasts. Second, the adoption of multimedia formats in 24/7 news network platforms has enhanced interactivity and reader engagement in the news process. However, the media industry faces challenges in dealing with this phenomenon. The demand to provide non-stop news puts pressure on journalists and editors to remain relevant and accurate in delivering information. Additionally, the emergence of social news platforms has brought new issues related to the validity and credibility of news. This article also highlights the social impact of 24/7 news networks. Easy access to news anytime and anywhere has influenced how society consumes news and interacts with information. Moreover, ethical questions arise on how to manage the information overload presented by 24/7 news networks without compromising the reliability of sources.